Dynamics of the xanthophyll cycle and non-radiative dissipation of absorbed light energy during exposure of Norway spruce to high irradiance - Stroch, Michal; Kuldová, Kristina; Kalina, Jirí; Spunda, Vladimír (Journal of plant physiology, 2008)
The response of Norway spruce saplings (Picea abies [L.] Karst.) was monitored continuously during short-term exposure (10 days) to high irradiance (HI; 1000micromol m(-2)s(-1)). Compared with plants acclimated to low irradiance (100micromol m(-2)s(-1)), plants after HI exposure were characterized by a significantly reduced CO(2) assimilation rate throughout the light response curve. Pigment contents varied only slightly during HI exposure, but a rapid and strong response was observed in xanthophyll cycle activity, particularly within the first 3 days of the HI treatment. Both violaxanthin convertibility under HI and the amount of zeaxanthin pool sustained in darkness increased markedly under HI conditions. These changes were accompanied by an enhanced non-radiative dissipation of absorbed light energy (NRD) and the acceleration of induction of both NRD and de-epoxidation of the xanthophyll cycle pigments. We found a strong negative linear correlation between the amount of sustained de-epoxidized xanthophylls and the photosystem II (PSII) photochemical efficiency (F(V)/F(M)), indicating photoprotective down-regulation of the PSII function. Recovery of F(V)/F(M) at the end of the HI treatment revealed that Norway spruce was able to cope with a 10-fold elevated irradiance due particularly to an efficient NRD within the PSII antenna that was associated with enhanced violaxanthin convertibility and a light-induced accumulation of zeaxanthin that persisted in darkness.
Keywords: transport elektronů; xanthofyly; Photosystem II Protein Complex; chlorofyl a; lutein; světlo; Photosynthesis; oxid uhličitý; zeaxanthiny; Lutein; epoxidové sloučeniny; Absorption; Carbon Dioxide; Zeaxanthins; Light; Chlorophyll; fotosyntéza; Electron Transport; absorpce; Fluorescence; chlorofyl; Time Factors; Picea; fotosystém II (proteinový komplex); smrk; časové faktory; Norway; Chlorophyll A; Xanthophylls; fluorescence; Norsko; Epoxy Compounds